Diagnosing the viability of functional analysis of a gene sequence process in multiple-recursive bioinformatics experimentalwork situations - Ibrahim, Roliana (Penerbit UTM Press, 2008)
The Functional Analysis of a Gene Sequence Process (FAoGS) is a process which requires molecular bench scientists to predict the function of a selected gene sequence. In order to predict a gene function, scientists conduct multiple and complex dry laboratory procedures. The focus of this paper is to explain the adaptation of two models; a Viable System Model (VSM) and Integrated Information Behaviour Model (IBM) for diagnosing the viability of multiple bioinformatics work procedures embedded in recursive work situations. Undertaking experimental work procedures in this kind of environment require scientists to access, use and integrate variety of biological data from heterogeneous information sources. This paper explains how the use of VSM and IBM support the modelling of dry bioinformatics work procedures in multiple-recursive embedded experimental work situations. This model allows systems analyst to identify the operational or autonomous work procedures at different recursion levels of work situations. The results or this analysis will allow systems analyst to understand and establish the existence of cohesive and adaptive mechanisms during FAoGS process in order to suggest appropriate design of Integrated Information Repository (IIR).